(untitled) (World Bulletin of Public Health, 2024)
Pregnancy failure is still an urgent problem of modern obstetrics. Despite the recent successes in the prevention and treatment of this pathology, the frequency of spontaneous miscarriages remains quite high. Thus, according to different authors, it ranges from 2 to 55%. In turn, as the number of spontaneous miscarriages increases, the risk of termination of subsequent pregnancies increases sharply [9, 12, 15, 19].